The STREGA survey – II. Globular cluster Palomar 12. Issue 3 (2nd October 2017) - Musella, I.; Di Criscienzo, M.; Marconi, M.; Raimondo, G.; Ripepi, V.; Cignoni, M.; Bono, G.; Brocato, E.; Dall'Ora, M.; Ferraro, I.; Grado, A.; Iannicola, G.; et al.
Abstract: In the framework of the STREGA (STRucture and Evolution of the GAlaxy) survey, two fields around the globular cluster Pal 12 were observed with the aim of detecting the possible presence of streams and/or an extended halo. The adopted stellar tracers are the main sequence, turn-off and red giant branch stars. We discuss the luminosity function and the star counts in the observed region covering about 2 tidal radii, confirming that Pal 12 appears to be embedded in the Sagittarius Stream. Adopting an original approach to separate cluster and field stars, we do not find any evidence of significant extra-tidal Pal 12 stellar populations. The presence of the Sagittarius stream seems to have mimicked a larger tidal radius in previous studies. Indeed, adopting a King model, a redetermination of this value gives r T = 0.22 ± 0.1 deg.